Glassy carbon electrode modified by new Copper(I) oxide nanocomposite for glucose detection: An electroanalysis study. (11th April 2019) - Karami, Kazem; Allafchian, Ali Reza; Amiri, Razieh; Shirani, Fatemeh; Bayat, Parvaneh; Rezaei, Behzad
Abstract : The Glucose amount of human blood is very vital because in higher levels than allowed value the corporal biological system was hampered. Therefore, in this study, the Cu2 O was deposited on the reduced Graphene oxide (RGO) by polydopamin (PDA) as linker. The new RGO‐PDA‐Cu2 O nanocomposite was deposited on the glassy carbon electrode (GCE) surface after its characterization by UV–Visible, fourier transform infrared (FT‐IR), X‐ray diffraction (XRD), Energy‐dispersive X‐ray (EDX), transmission electron microscopy (TEM) and field emission scanning electron microscopy (FESEM) techniques. The electroanalysis of the new electrode was investigated by the cyclic voltammetry (CV), differential pulse voltammetry (DPV) and electrochemical impedance spectroscopy (EIS) methods. The obtained detection limit of glucose (Glu) showed that the deposited GCE by RGO‐PDA‐Cu2 O nanocomposite has a high potential for its diagnosis. In addition, this electrode was applied to the Glu detection as biosensor in real samples in order to utilize in commercial applications. Abstract : In this research, the Cu2 O was deposited on reduced Graphene oxide (RGO) by polydopamin (PDA) as linker. The new RGO‐PDA‐Cu2 O nanocomposite was deposited on the glassy carbon electrode (GCE) surface after its characterization. The electroanalysis of the new electrode was investigated by the cyclic voltammetry (CV), differential pulse voltammetry (DPV) and electrochemical impedance spectroscopy (EIS) methods. The detection limit of glucose (Glu) showed that the deposited GCE by RGO‐PDA‐Cu2 O nanocomposite has a high potential for its diagnosis.